2020
DOI: 10.3390/ijerph17155450
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Clostridium Perfringens Isolates Collected from Three Agricultural Biogas Plants over a One-Year Period

Abstract: Digestate produced by agricultural biogas plants (BGPs) may contain pathogenic bacteria. Among them, Clostridium perfringens deserves particular attention due to its ability to grow under anaerobic conditions and persist in amended soil. The aim of this study was to examine the potential pathogenicity and the antimicrobial resistance of C. perfringens in manure and digestate collected from three agricultural biogas plants (BGPs). A total of 157 isolates (92 from manure, 65 from digestate) were screened for gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…Currently, some antibiotics are allowed for treating NE in poultry production. However, the improper use of antibiotics results in drug resistance in C. perfringens and increases public concerns regarding residual drugs in animal products ( Derongs et al, 2020 ). This situation underscores an urgent need for a natural alternative in poultry production ( Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…Currently, some antibiotics are allowed for treating NE in poultry production. However, the improper use of antibiotics results in drug resistance in C. perfringens and increases public concerns regarding residual drugs in animal products ( Derongs et al, 2020 ). This situation underscores an urgent need for a natural alternative in poultry production ( Lu et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Apart from CPE, beta2 toxin encoded by the cpb2 gene has been associated with enteric disease in humans and necrotic enteritis in chickens and many other animal species. 7,9,10 A recent study suggested that beta2 toxin was significantly associated with children suffering from autism spectrum disorders (ASD). 11 Multi-locus sequence typing (MLST) is a commonly used technique for the typing of human, animal and foodborne pathogens.…”
Section: Introductionmentioning
confidence: 99%
“…Although Clostridium species are acclimatised to biogas environments [ 10 , 34 , 35 , 36 ] and are known to be involved in the hydrolytic and acidogenic stages of the AD process [ 4 ], ISRs 0.25 and 0.50 achieved 2 log 10 and 1.5 log 10 decrease in counts, respectively. This also agrees with the work of Fontana et al [ 21 ], who observed a slight decrease in the number of culturable Clostridium spores in the digestate compared with the inoculum during continuous mesophilic AD.…”
Section: Discussionmentioning
confidence: 99%